Modern museums in the palaces of the western Grasfields, Cameroon - Fubah, Mathias Alubafi (Afrika Focus, 2016)
This paper suggests that the recent interest in modern museums in the palaces of the Grassfields is obscurely associated with the need to transform the palaces and, more importantly to address the multiple problems plaguing the royal treasury or traditional palace museums. The paper argues that unlike the royal treasury, the modern museum is significant, partly because it constitutes a democratic space, and partly because it articulates and can be associated with the irony of change and continuity. Method: The findings are based on qualitative data collected from documents and from ethnographic studies on the emergence of modern museums across the region. Results: The paper has contributed to the scholarship on Cameroon, and, in particular, extended Michael Rowlands’ (2008) seminal work on curating postcolonial pasts in the Grass elds by unveiling the modern museum as a democratic lens through which to view the undemocratic royal treasury. Policy implications: The study suggests among others, the need for the Grassfields population to embrace the modern museum – and to see it as a continuation of the royal treasury. The practical implication is to tailor the modern museum to the socio-cultural needs of the target population-particularly women and youths since they are generally excluded from the activities of the royal treasury. Key words : royal treasury, museum, Cameroon, Grassfields, Bambui, youths